Pelatihan Pembacaan Al-Qur’an Bit Tartil Berbasis Media Digital Bagi Siswa Madrasah Ibtidaiyah Miftahul Ulum - Luthviyah Romziana; Hilda Wardatul Jannah; Fika Khoirina A.S; Intan Prasari (Yayasan Mutiara Hati Moeslem, 2026)
This Community Service Program (PKM) focuses on training students of Madrasah Ibtidaiyah Miftahul Ulum in bit tartil Qur’anic recitation through the use of digital media. The program aims to improve the quality of students’ Qur’an recitation, particularly in terms of accurate pronunciation of makhraj (articulation points), application of basic tajwid rules, and fluency in tartil, while addressing the limitations of conventional teaching methods that have been commonly used. The method employed a descriptive qualitative approach consisting of preparation, implementation, evaluation, and follow-up stages. The solutions provided included the use of tartil audio-visual media, digital voice recordings as a tool for evaluating recitation, and teacher mentoring to strengthen digital literacy in Qur’anic learning. The results indicate a significant improvement in students’ recitation quality, increased learning enthusiasm, and greater ease for teachers in conducting more objective and efficient recitation assessments. The use of digital media proved effective in accommodating variations in students’ abilities and overcoming teachers’ limited time for correction. Therefore, the integration of digital media in Qur’anic learning not only enhances the accuracy of students’ recitation but also strengthens teachers’ capacity to conduct continuous evaluation. Future efforts require sustained mentoring and institutional support to enable wider and more sustainable implementation of this digital-based bit tartil learning model.